Wealth creation from commercialisation of R&D Products real life experiences of Malaysian - Mohd. Jailani Mohd. Nor; Norain Ismail; Safiah Sidek (Penerbit Universiti Teknikal Malaysia Melaka, 2015)
This is a book of enormous significance as it highlights the importance of having a carefully planned strategy for a successful implementation of R&D products